Green sustainable “lemang” toaster machine / Bakri Ali, Aminuddin Hamid and Nurrafiqah Sabree - Ali, Bakri; Hamid, Aminuddin; Sabree, Nurrafiqah (2021)
Lemang is a favorite Malay cuisine in Malaysia especially during the festive season, or Hari Raya. Traditional lemang making process which uses firewoods as a source of heat and bamboo tree as a container contributes to an environmental problem due to the burning and cutting of wood and bamboo. It also causes health problems to humans due to air pollution and long exposure to direct heat. This innovation’s objective is to design and fabricate a green sustainable lemang toaster. This innovation hopefully will help lemang sellers to save time and energy as well as save the environment from tree cutting and open burning. The novelty or uniqueness of the product are the heating source which uses natural gas to reduce environmental pollution and its cooking barrel/container that uses stainless steel tubes to reduce cutting and burning bamboo trees. The special feature of this product is it does not use bamboo, firewood, charcoal, and so on. The barrel can also rotate on its own with the help of a dc motor, performing the baking or toasting process without intensive care. Its impacts will reduce environmental problems, reduce cooking time, produce effective heat circulation, and need a minimum observation or maintenance making it a user friendly tool. The potential customers can be lemang business owners or producers, as well as personal users especially lemang lovers making it potential to be commercialised.